A critical assessment of dose effects of post‐thaw CD34 on autologous stem cell transplantation treatment of haematological malignancies - Gustavo de Carvalho Duarte; Andrew Butler; Gavin Atkinson; Krishna Badami; Wen‐Hua Wei (eJHaem, 2023)
Abstract A consensus threshold of pre‐cryopreservation CD34‐positive cells (CD34s) has been used as the minimum dose to initiate autologous stem cell transplantation (ASCT). Advances in cryopreservation posed a debate whether post‐thaw CD34s might be a superior surrogate instead. We addressed the debate in this retrospective study of 217 adult ASCTs in five different haematological malignancies treated at a single centre. We showed that post‐thaw CD34s was highly correlated with pre‐cryopreservation CD34s (r = 0.97) and explained ∼2.2% (p = 0.003) of the variation of the post‐thaw total nucleated cell viability that however had no power to predict engraftment outcomes. After stratifying the ASCT cases into four dose groups based on post‐thaw CD34s reinfused, stepwise multivariate regression analyses detected significant effects in dose group and interactions with diseases for neutrophil and platelet recovery respectively. The significant dose effects and interactions were triggered by two technical outliers in the low dose group, and disappeared in the repeated regressions after exclusion of the outliers where disease and age were the significant predictors remained. Our data clearly support the validity of the consensus threshold in ASCT applications but also highlight neglected conditions where monitoring post‐thaw CD34s and clinical attributes are valuable.